2017
DOI: 10.1177/0269881117705088
|View full text |Cite
|
Sign up to set email alerts
|

Patient emergency assessment following deliberate self-poisoning with benzodiazepines: Can cognitive markers predict recall of the psychiatric interview? A pilot study

Abstract: Attentional functions tested by WAIS Coding test and TMT A were correlated with memory score. It could be profitable to assess it in clinical practice prior to a psychiatric interview.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…The main outcome of this study is its confirmation of the findings of our pilot study (Salles et al, 2017), which showed the WAIS coding attentional cognitive test is the best when it comes to predicting the good memorization of a psychiatric interview.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The main outcome of this study is its confirmation of the findings of our pilot study (Salles et al, 2017), which showed the WAIS coding attentional cognitive test is the best when it comes to predicting the good memorization of a psychiatric interview.…”
Section: Discussionsupporting
confidence: 66%
“…Indeed, little is known about which cognitive tests could be used in the ED after intentional self-poisoning. A pilot study was conducted by Salles et al (2017) in which the authors examined several cognitive tests to determine their association with a memory score. The results showed the Wechsler Adult Intelligence Scale (WAIS) coding test and the Trail Making Test, Part A (TMT A), two tests that address the attention function, were the most performant when it comes to predicting episodic memory of a psychiatric assessment after discharge.…”
Section: Introductionmentioning
confidence: 99%